Microbiology: lessons from a first attempt at Lake Ellsworth - Pearce, David; Magiopoulos, Iordanis; Mowlem, Matt; Tranter, Martyn; Holt, Giles; Woodward, John; Siegert, Martin (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2015)
During the attempt to directly access, measure and sample Subglacial Lake Ellsworth in 2012–2013, we conducted microbiological analyses of the drilling equipment, scientific instrumentation, field camp and natural surroundings. From these studies, a number of lessons can be learned about the cleanliness of deep Antarctic subglacial lake access leading to, in particular, knowledge of the limitations of some of the most basic relevant microbiological principles. Here, we focus on five of the core challenges faced and describe how cleanliness and sterilization were implemented in the field. In the light of our field experiences, we consider how effective these actions were, and what can be learnt for future subglacial exploration missions. The five areas covered are: (i) field camp environment and activities, (ii) the engineering processes surrounding the hot water drilling, (iii) sample handling, including recovery, stability and preservation, (iv) clean access methodologies and removal of sample material, and (v) the biodiversity and distribution of bacteria around the Antarctic. Comparisons are made between the microbiology of the Lake Ellsworth field site and other Antarctic systems, including the lakes on Signy Island, and on the Antarctic Peninsula at Lake Hodgson. Ongoing research to better define and characterize the behaviour of natural and introduced microbial populations in response to deep-ice drilling is also discussed. We recommend that future access programmes: (i) assess each specific local environment in enhanced detail due to the potential for local contamination, (ii) consider the sterility of the access in more detail, specifically focusing on single cell colonization and the introduction of new species through contamination of pre-existing microbial communities, (iii) consider experimental bias in methodological approaches, (iv) undertake in situ biodiversity detection to mitigate risk of non-sample return and post-sample contamination, and (v) address the critical question of how important ...